The relationship between providing a balanced menu and the incidence of stunting in toddlers in Lembar Selatan village - Aryani, Ni Putu; Afrida, Baiq Ricca (Alma Ata University Press, 2025)
Background: Stunting is a condition of growth failure in toddlers due to chronic malnutrition, repeated infections, and inadequate stimulation, characterized by a height that is lower than the standard for their age (Z-score <-2 SD).Stunting affects learning achievement, cognitive development, and physical growth. Stunting also increases the risk of non-communicable diseases, including diabetes and heart disease, in adulthood.Objectives: This research aims to determine the relationship between the frequency of stunting in toddlers in South Lembar Village, Lembar District, West Lombok Regency and the availability of balanced nutrition. Stunting is a health issue that may adversely affect physical growth, cognitive development, and future productivity. Factors contributing to stunting include insufficient dietary intake, infections, inadequate sanitation, and socio-economic conditions.Methods: The used research technique is observational analytic using a cross-sectional strategy. The research sample included 213 moms of toddlers. Data were gathered via questionnaires about maternal attributes, feeding practices, and the nutritional health of children.Results: Bivariate analysis using the Chi-Square test revealed a significant association between the provision of a balanced food (p = 0.017), supplementary feeding (p = 0.009), and exclusive nursing (p = 0.000) and the nutritional status of toddlers.Conclusions: The study's findings underscore the significance of adequate nutrition for toddlers in mitigating stunting. Consequently, enhancing parental education on good eating habits and improving availability to nutritious food is essential to mitigate stunting rates in Indonesia.